Cattle’s behaviour – perceptions, relationships, studies and measurements of temperament - Hervé, Jeremy; Szentléleki, Andrea; Tőzsér, János (Animal welfare, Ethology and Housing Systems (AWETH), 2007)
Nowadays, the evolution of the worldwide agriculture has come to raise new aspects, and animal welfare is one of them. The measurement of cattle’s behaviour and its assessment has consequently become more and more important. However, basic knowledge of general and applied ethology are needed in order to measure behaviour and draw conclusions. The authors’ aim was to summarize and explain this basic information in order to support further studies about cattle’s behaviour. For this purpose, the environmental perceptions of animals have been looked over to understand how animals have connection with their surroundings. Then, relationships of an animal with other animals of the same species and with humans have been detailed before to focus on temperament described as the reaction that an animal shows in response to a stimulation of its external environment. As measuring temperament under different test conditions is the main way of determining the behavioural type of animals, so the different methods of measurement also had to be explained. Finally, all knowledge in this review are suggested to use for further studies concerning animal behaviour.
Keywords: cattle behaviour; perception; human-animal relationship; temperament